Configuración y reconfiguración de la identidad profesional docente: entre la experiencia escolar y la práctica reflexiva - Torres-Valderrama, Sebastián (2025)
The aim of this essay is to explore that the Professional Teaching Identity is configured and reconfigured through School Experiences and Reflective Practice. It is argued that Biographical Marks, formed by significant interactions in the school stage, directly influence Professional Identity. Reflective Practice is presented as an essential tool to re-signify these experiences, allowing future teachers to develop pedagogical strategies and strengthen their professional identity. As a result, tensions between institutional expectations and personal experiences are identified, as well as inequalities in the implementation of reflective practices in different educational contexts. It is concluded that the life histories of Initial Teacher Education students should be integrated and their reflection promoted to reduce the gap between theory and practice. This dynamic process of configuration and reconfiguration of teacher identity requires a constant dialogue between what has been experienced, what has been learned and what has been reflected upon.